Expression of 11beta-hydroxysteroid dehydrogenase type 1 in adipose tissue is not increased in human obesity. - Tomlinson, J; Sinha, B; Bujalska, I; Hewison, M; Stewart, P (2002)
Central obesity is associated with increased morbidity and mortality. Preadipocyte proliferation and differentiation contribute to increases in adipose tissue mass, yet the mechanisms that underlie these processes remain unclear. Patients with glucocorticoid excess develop a reversible form of central obesity, but circulating cortisol levels in idiopathic obesity are invariably normal. We have hypothesized that the enzyme 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1), by converting inactive cortisone to active cortisol in adipose tissue, might be an important autocrine regulator of fat mass. Paired omental and sc fat biopsies were obtained from 32 women (median age, 43 yr; range, 28-65; median body mass index, 27.5 kg/m(2); range, 19.7-39.2) undergoing elective abdominal surgery. 11beta-HSD1 activity and mRNA levels were assessed in whole tissue and in isolated preadipocytes and adipocytes using specific enzyme assays and real-time PCR. Preadipocyte proliferation was measured using tritiated thymidine incorporation. Whole adipose tissue 11beta-HSD1 mRNA levels did not differ between omental and sc samples (P = 0.73). In addition, mRNA levels did not correlate with body mass index (omental: r = 0.1; P = 0.6; sc: r = 0.15; P = 0.4). In keeping with earlier studies, 11beta-HSD1 mRNA levels were higher in omental compared with sc preadipocytes. However, in cultured omental preadipocytes, 11beta-HSD1 activity inversely correlated with body mass index (r = -0.47; P = 0.03). In omental preadipocytes, both cortisol and cortisone decreased proliferation (P < 0.05). Inhibition of 11beta-HSD1 with glycyrrhetinic acid partially reversed the cortisone-induced decrease in preadipocyte proliferation (P < 0.05). Enhanced preadipocyte proliferation within omental adipose tissue as a consequence of decreased 11beta-HSD1 mRNA levels and activity may contribute to increases in visceral adipose tissue mass in obese patients.